Persistence of immunity following 2-dose priming with a 10-valent pneumococcal conjugate vaccine at 6 and 10 weeks or 6 and 14 weeks of age in Nepalese toddlers - Gurung, M; Bijukchhe, SM; Hariri, P; Voysey, M; Kandasamy, R; Thorson, S; Maskey, P; Pandit, R; Shrestha, B; Gautam, MC; Maharjan, M; Lama, L; et al. (Lippincott, Williams & Wilkins, 2021)
Background: The pneumococcal conjugate vaccine has had a substantial impact on invasive pneumococcal disease. Previously, we compared immunity following vaccination with the 10-valent pneumococcal conjugate vaccine (PCV10) administered at 2 slightly different schedules: at 6 and 10 weeks of age, and at 6 and 14 weeks of age, both followed by a 9-month booster. In this study, we followed up those participants to evaluate the medium-term persistence of serotype-specific pneumococcal immunity at 2-3 years of age.